The phenomenon of school absence among middle school students – A case study on the eleventh middle school students in Al-Rass city – - Alharbi, Baryh Hamoud (Journal of Educational and Psychological Sciences, 2021)
This study aims to research the causes of absence in middle school, to examine them through the field of application of (the eleventh middle school in Al-Rass city) from the point of view of the students, and from the point of view of the educational and administrative staff and to identify the reasons for the repeated absence of students, the study uses the case study methodology. The school consists of 201 people a 171 students and 23 teachers, and 7 administrative staff , the study reached a number of outstanding results: The main reason for the absence is the emergence of a secondary interests, also that the average number of absent students every day is 28 which represents 13% of the total number of students in the school, and in light of these results the researcher suggests a number of approaches that can help to reduce the absence of middle school students.